The effectiveness of preventive annotation in the protection of property. - Orozco Reinaga, Ernesto Joel (2013)
Objetive: Consolidate the figure of the Preventive Annotation  (Registration Law), as a protective institution Predial property.  Method: In essence, was treated in a social research since the  field work was to the company and human events (professionals,  user registration, public servants, etc.) And specialized, as was  done from the particular perspective Registration Law. Data  collection was conducted by thesis student, supported by  advisers (books, documents and guidance) and made the  necessary arrangements with the reality that provided the  information: Registry Office of Arequipa (File and Registry  Area Sections).  Results: figure consolidates notation as a protective institution  built property. Upon completion of the investigation, it was  observed that it was developed under the study parameters, but  made after the analysis of the collected data could be obtained  two proposals to amend national legislation, which were not  provided for in the draft research. I'm referring to - just - to the  notation for contradictory title, which involves modification of  the General Regulations of the Public Records, and the  requirement to request annotation injunction demand (as  demand admisorio requirement) in all processes where  registered rights is discussed, which involves modifying the  Civil Procedure Code. These two aspects (proposed changes)  arise from the research itself, but it was not provided for in Thesis  Project.  Conclusion: That notation is an effective and protective of  property title (high grade), but knowledge of this legal is  minimal, not only by users but also by operators right (public  records, lawyers of Public Records, Public Notaries lawyers and  independent lawyers).